ISLAM, CHRISTIANITY, AND INDIGENOUS BELIEFS IN DIALOGUE: The Dynamics of Religious Coexistence in Indonesia’s Peripheries - Kadenun, Kadenun; Abdurrohman, Moh Asvin (Asia-Pacific Journal on Religion and Society, 2024)
This article explores the dynamics of interreligious relations in three peripheral communities of Indonesia—Jayapura (Papua), Sidenreng Rappang (South Sulawesi), and Dusun Sonyo (Yogyakarta)—based on an analytical reading of Hasse Jubba’s ethnographic work (2017). Using a qualitative approach rooted in ethnographic content analysis, the study examines how Muslims, Christians, Buddhists, and local religious communities (Towani Tolotang) sustain coexistence through social mechanisms, cultural values, and shared rituals. The findings reveal that interreligious relations at the grassroots level are not primarily shaped by formal state regulations or theological dialogue, but rather by everyday encounters, economic collaboration, and communal solidarity. The theoretical frameworks employed include structural functionalism, practical multiculturalism, interfaith dialogue models (Knitter), and ritual-symbolic theory (Turner). The three cases demonstrate that peripheral communities possess strong cultural capacities to manage religious diversity through pragmatic interfaith engagements and contextual collective spirituality. This study contributes to rethinking pluralism as a locally grounded, socially enacted, and spiritually embedded practice beyond formal frameworks.